A shower of mid-infrared Raman solitons at designed wavelength of ∼3 μm from a tapered fluorotellurite fiber. (2nd August 2021) - Guo, Xiaohui; Li, Zhenrui; Jiao, Yadong; Zhao, Zhipeng; Yao, Chanfei; Jia, Zhixu; Dong, Kegong; Zhang, Haoyu; Lin, Honghuan; Qin, Weiping; Qin, Guanshi
Abstract: Optical temporal soliton generation in optical fibers and resonators has achieved great breakthroughs and found significant applications in many fields. Despite recent advances on optical soliton generation in optical fibers, it remains challenging to realize a shower of Raman solitons at a certain wavelength in optical fibers, i.e. put all the generated Raman solitons at a same wavelength on demand. Here we propose and experimentally demonstrate a shower of mid-infrared Raman solitons at designed wavelength of 3 μ m from a tapered fluorotellurite fiber pumped by a 1960 nm picosecond fiber laser. Tapered fluorotellurite fibers have an untapered region length of ∼49 cm and a tapered transition region length of ∼1 cm. The fiber segment at the end of the tapered region has a 2nd zero-dispersion wavelength of ∼3 μ m. Firstly, multiple Raman solitons with different wavelengths are generated in the untapered region pumped by the 1960 nm picosecond laser. Then, as Raman solitons propagate into the tapered region, the redshift of all the generated Raman solitons with different wavelengths are accelerated due to the dramatic increase of the nonlinear coefficient. Finally, as Raman solitons move out from the tapered region, all the accelerated Raman solitons are stopped around 3 μ m owing to the occurrence of soliton self-frequency shift cancellation, causing the generation of a shower of mid-infrared Raman solitons around 3 μ m. This phenomenon may find applications in super-efficient nonlinear light generation and signal processing.